Improvement of head and neck range of motion induced by chronic pallidal deep brain stimulation for cervical dystonia - Blahak, Christian; Wolf, Marc; Saryyeva, Assel; Bäzner, Hansjörg; Krauss, Joachim K. (Journal of neural transmission, 2021)
Deep brain stimulation (DBS) of the globus pallidus internus (GPi) has become an accepted treatment for severe cervical dystonia (CD). Assessment of therapeutic efficacy of DBS mostly focused on head position at rest but hardly on limitations of head and neck mobility, which represent a functionally important impairment in CD.